Non-murine models to investigate tumor-immune interactions in head and neck cancer - Rossa, Carlos [UNESP]; D’Silva, Nisha J. (Springer Nature, 2019)
The immune response has important roles in the biology of solid tumors, including oncogenesis, tumor growth, invasion and metastasis, and response to treatment. Improved understanding of tumor-immune system interactions has provided promising therapeutic options that are based on the rescue and enhancement of the anti-tumoral host response. Immune-based treatments have been approved for clinical use in various types of cancer, including head and neck cancer (HNC); other strategies involving combination therapies are currently in development. These novel therapies were developed based on knowledge derived from in vitro, in silico, and in vivo pre-clinical studies. However, clinical trials seldom replicate the efficacy observed in pre-clinical animal studies. This lack of correlation between pre-clinical studies and clinical trials may be related to limitations of the models used; which highlights the relevance of considering immune-related aspects of different pre-clinical models. Murine models are the most frequently used pre-clinical models of HNC and are discussed elsewhere. Non-murine models have characteristics that offer unique opportunities for the study of HNC etiology, therapeutic strategies, and tumor-immune system interactions. The current review focuses on immune-related aspects of non-murine models, including dog, cat, pig, zebrafish, and frog, that could be used to investigate tumor-immune interactions in HNC.